Effects of ischaemic conditioning on major clinical outcomes in people undergoing invasive procedures: systematic review and meta-analysis. (7th November 2016) - Sukkar, Louisa; Hong, Daqing; Wong, Muh Geot; Badve, Sunil V; Rogers, Kris; Perkovic, Vlado; Walsh, Michael; Yu, Xueqing; Hillis, Graham S; Gallagher, Martin; Jardine, Meg
Abstract : Objective  To summarise the benefits and harms of ischaemic conditioning on major clinical outcomes in various settings. Design  Systematic review and meta-analysis. Data sources  Medline, Embase, Cochrane databases, and International Clinical Trials Registry platform from inception through October 2015. Study selection  All randomised controlled comparisons of the effect of ischaemic conditioning on clinical outcomes were included. Data extraction  Two authors independently extracted data from individual reports. Reports of multiple intervention arms were treated as separate trials. Random effects models were used to calculate summary estimates for all cause mortality and other pre-specified clinical outcomes. All cause mortality and secondary outcomes with P<0.1 were examined for study quality by using the GRADE assessment tool, the effect of pre-specified characteristics by using meta-regression and Cochran C test, and trial sequential analysis by using the Copenhagen Trial Unit method. Results  85 reports of 89 randomised comparisons were identified, with a median 80 (interquartile range 60-149) participants and median 1 (range 1 day-72 months) month intended duration. Ischaemic conditioning had no effect on all cause mortality (68 comparisons; 424 events; 11 619 participants; risk ratio 0.96, 95% confidence interval 0.80 to 1.16; P=0.68; moderate quality evidence) regardless of the clinical setting in which it was used or the particular intervention related characteristics. Ischaemic conditioning may reduce the rates of some secondary outcomes including stroke (18 trials; 5995 participants; 149 events; risk ratio 0.72, 0.52 to 1.00; P=0.048; very low quality evidence) and acute kidney injury (36 trials; 8493 participants; 1443 events; risk ratio 0.83, 0.71 to 0.97; P=0.02; low quality evidence), although the benefits seem to be confined to non-surgical settings and to mild episodes of acute kidney injury only. Conclusions  Ischaemic conditioning has no overall effect on the risk of death. Possible effects on stroke and acute kidney injury are uncertain given methodological concerns and low event rates. Adoption of ischaemic conditioning cannot be recommended for routine use unless further high quality and well powered evidence shows benefit.